Screening of developmental dysplasia of the hip in the newborns - Mohamad Ah. Jasim; Bashar Sh. Mustafa (University of Mosul, 2011)
Background: Newborn babies are known to have risk for occurrence developmental dysplasia of the hip so early clinical screening test is very important to detect this problem and prevent further abnormal growth. The aim of this study is to find the rate of occurrence of developmental dysplasia of the hip (DDH) among newborn babies and establish good screening program. Patients and methods: From August ٢٠٠٦ to March ٢٠٠٩ in AL-Khansaa Maternity and Children Teaching hospitals, ٩٥٩٢ newborn babies were examined clinically using Barlows and ortolani tests for detecting DDH. Results: Only ١٦٢ newborn babies out of ٩٥٩٢ examined babies had DDH and it was found more common among female and more on left side than right side. Female sex, rural residence, first born baby breach, caesarean section positive family history, multiple pregnancy post-mature babies, high birth weight (>٣٥٠٠ g). Conclusion: The occurrence of neonatal DDH is still form a major problem among newborn babies causing a lot of morbidity need to follow up to avoid further complicating problem.